Rearranging the Chairs on the Deck or True Reform? Private Sector Bureaucracies in the Age of Choice—An Analysis of Autonomy and Control. Issue 1 (January 2020) - Jessen, Sarah Butler; DiMartino, Catherine
This article uses edvertising as a vehicle through which to examine autonomy and control for key agents in education when market-like reforms are combined with privately led management of schools. We begin by outlining the philosophical foundations of school choice from the perspective of autonomy and control, and then lay out the case of edvertising. Guided by Cribb and Gewirtz's theoretical discussion of autonomy and control, we explore degrees and types of autonomy and control for various agents in schools. We then examine the differences between levels of autonomy for key agents—schools, principals, teachers, parents, and the State—as idealized in the philosophical underpinning of market-based policies with the actual autonomy exhibited with the introduction of edvertising.